Belajar system peredaran darah manusia SD kelas 5 menggunakan metode PjBL(project based learning) SD Negeri Jenggrik 3 Kedawung Sragen - Permatasari, Evy (Universitas Sebelas Maret, 2022)
Learning is a change in the behavior of someone who has learned from knowledge (don't know to know), skills (can't become able) and attitude (don't care to care). The circulatory system or what is usually called the circulatory system is an organ system that functions to move substances and nutrients from cells. Project Based Learning is a learning method that uses projects/activities as a medium. Students carry out exploration, assessment, interpretation, synthesis and information to produce various forms of learning outcomes. Project-based learning (PjBl) with the support of Power Point (PPT) media in this class not only inspires creativity but also prepares students to face real world challenges. They not only learn concepts but also solve problems and apply knowledge in real world contexts. Interesting learning such as project-based learning stimulates students' creativity and critical thinking abilities. This research aims to improve academic achievements or student outcomes by implementing the Project Based Learning (PjBL) learning model in the 5th grade Human Blood System subject at Jenggrik 3 Kedawung State Elementary School, Sragen.